Analisis Penerapan Akuntansi Dana Kas Kecil (Petty Cash) pada PT Ingress Technologies Indonesia - Nuraini, Nurin; Rahma, Madjidainun (Jurnal Ilmiah Wahana Pendidikan, 2024)
The role of accounting is very important for accurate results and ensuring accuracy in recording procedures as well as preventing deviations or embezzlement of company petty cash funds. This research aims to find out how petty cash accounting is implemented at PT Ingress Technologies Indonesia. The analysis technique used is a qualitative descriptive analysis technique carried out by describing the application of petty cash accounting in companies, which relates to the method of recording petty cash, documents and accounting records used, functions related to recording petty cash, and procedures for implementing petty cash records. Data collection was carried out through interviews, observation, literature and documentation. Based on research results from PT Ingress Technologies Indonesia, it shows that the implementation of petty cash accounting is completely good, and in accordance with applicable theory. It's just that only one person in the accounting department carries out petty cash records and is also tasked with working on or compiling the company's financial reports. In this case, petty cash fund holders are vulnerable to not being able to control their work because they have too much work and are very vulnerable to fraud and embezzlement of funds committed when recording petty cash.